Pengaruh Promosi dan Kualitas Layanan Terhadap Keputusan Penggunaan Shopee Pinjam (Spinjam) di Kota Surabaya - Siti Aisah; Laurencya Aurora; Iswati; Rosita Febrianti (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to analyze the influence of promotion and service quality on the decision to use Shopee Pinjam in Surabaya. The research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to 100 respondents who are Shopee Pinjam users in Surabaya, selected using purposive sampling techniques. Data analysis was conducted using multiple linear regression to determine the simultaneous and partial effects of the promotion and service quality variables on the decision to use Shopee Pinjam. The results indicate that promotion has a positive and significant influence on the decision to use Shopee Pinjam. Similarly, service quality also has a positive and significant effect on the decision to use Shopee Pinjam. Furthermore, both promotion and service quality simultaneously have a significant impact on the decision to use Shopee Pinjam.